Pengaruh Pembentukan Pelat Baja Galvanil Ketebalan 0,8 mm Melalui Metode Bead Rolled Terhadap Kekakuan - Indra Adipura, Anandri; Erwanto, Erwanto; Darta, Yuli (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
The manufacturing industry, particularly in the automotive sector, galvanized steel sheets are commonly used due to their strong durability and high rigidity, making them suitable as structural components for vehicle bodies. However, the rigidity of galvanized steel sheets can be affected when formed under cold conditions. Therefore, this study aims to investigate the impact of cold forming on the natural frequency of 0.8 mm thick galvanized steel sheets. Using the Vibroport 80 device, the sheets were formed into cross grooves and then clamped onto a test fixture as part of the testing procedure. Taguchi's method was employed to analyze the data. Based on the research results using Taguchi, the Signal-to-Noise (S/N) ratio for stiffness with the